Humans and elephants as treefall drivers in African savannas. Issue 11 (19th January 2017) - Mograbi, Penelope J.; Asner, Gregory P.; Witkowski, Ed T. F.; Erasmus, Barend F. N.; Wessels, Konrad J.; Mathieu, Renaud; Vaughn, Nicholas R.
Abstract : Humans have played a major role in altering savanna structure and function, and growing land‐use pressure will only increase their influence on woody cover. Yet humans are often overlooked as ecological components. Both humans and the African elephant Loxodonta africana alter woody vegetation in savannas through removal of large trees and activities that may increase shrub cover. Interactive effects of both humans and elephants with fire may also alter vegetation structure and composition. Here we capitalize on a macroscale experimental opportunity – brought about by the juxtaposition of an elephant‐mediated landscape, human‐utilized communal harvesting lands and a nature reserve fenced off from both humans and elephants – to investigate the influence of humans and elephants on height‐specific treefall dynamics. We surveyed 6812 ha using repeat, airborne high resolution Light Detection and Ranging (LiDAR) to track the fate of 453 685 tree canopies over two years. Human‐mediated biennial treefall rates were 2–3.5 fold higher than the background treefall rate of 1.5% treefall ha –1, while elephant‐mediated treefall rates were 5 times higher at 7.6% treefall ha –1 than the control site. Model predictors of treefall revealed that human or elephant presence was the most important variable, followed by the interaction between geology and fire frequency. Treefall patterns were spatially heterogeneous with elephant‐driven treefall associated with geology and surface water, while human patterns were related to perceived ease of access to wood harvesting areas and settlement expansion. Our results show humans and elephants utilize all height classes of woody vegetation, and that large tree shortages in a heavily utilized communal land has transferred treefall occurrence to shorter vegetation. Elephant‐ and human‐dominated landscapes are tied to interactive effects that may hinder tree seedling survival which, combined with tree loss in the landscape, may compromise woodland sustainability.